Anthropogenic influences in the Balaton Basin - Gulyás, László; Nagy, Miklós Mihály (Acta Scientiarum Socialium, 2013)
Anthropogenic influences in the Balaton Basin The academic investigations of the characteristics of Hungary’s largest lake, Lake Balaton is a glorious chapter in the history of geographical research in the country; research results have made Hungarian geography deservedly famous. Owing to the success of the Balaton research gaining momentum in the 1890s, the lake and its environs have become one of the best described areas in the Carpathian Basin. The imposing intensity and large volume of this work was demonstrated by a collection of a large number of publications, the so-called Balaton monography (Sándor Kozocsa 1939). Research participants, mainly scientists, could rightly be proud of their achievements (J. Cholnoky et.al.), although their work cannot be regarded as complete. (B. Bulla 1958). Despite the stormy 20th century history of Hungary the Balaton research programs could continue after shorter or longer periods of interruptions. But, even in these intensive research periods not enough attention was given to the historical geography of the lake and its environs. It was László Bendefy, a geographer-engineer and science historian, whose role needs to be emphasised (D. Balázs 1993; F. Fodor 2006) in this respect, and, who, as co-author, published the major historical geographical data of the Balaton Basin. (L. Bendefy L.-Nagy V. I. 1969). When considering the general nature of this work it can be concluded that, although it is a work of significance, but it was not able to describe fully the role geography played in changing the travel habits of Europeans and the ways how mass tourism contributed to the changing of the system of geographical conditions in the Balaton region. Our study aims to introduce the history of the impact of anthropogenic geographical factors that formed the Balaton Basin by applying the point of view of travel history. At the same time our attempt can be regarded as new research methodology since it aimed to apply a joint historical-geographical approach.